Respostas

2013-11-17T19:29:19-02:00
-9x^2=-1
-9x^2+1=0
Δ = b² -4ac
Δ = 0² -4 *(-9) * 1
Δ = 0 + 36
Δ = 36
x' = (-b + √∆)/ 2a
(-0 + 6)/2 * (-9)
(0 + 6)/-18
6/-18= -0,333333333333333
x'' = (-b - √∆)/ 2a
(-0 - 6)/2 * (-9)
(0 - 6)/-18
-6/-18= 0,333333333333333
-9x2= -1
x2= 1/9 e x= raiz quadra de 1/9 resposta x= 1/3
ou -1/3
  • Usuário do Brainly
2013-11-17T19:32:49-02:00
- 9 x^{2} = 5 - 6
- 9 x^{2} = - 1 .(-1)
9 x^{2} = 1
 x^{2}  \frac{1}{9}
x = +-  \sqrt{1/9}
x = +-  \frac{1}{3}

x = +  \frac{1}{3}
x = -   \frac{1}{3}
1 5 1